Modified methylenedioxyphenol analogs lower LDL cholesterol through induction of LDL receptor expression - Ying, Zhekang (The American Society for Biochemistry and Molecular Biology, 2012)
Although statin therapy is a cornerstone of current low density lipoprotein (LDL)-lowering strategies, there is a need for additional therapies to incrementally lower plasma LDL cholesterol. In this study, we investigated the effect of several methylenedioxyphenol derivatives in regulating LDL cholesterol through induction of LDL receptor (LDLR). INV-403, a modified methylenedioxyphenol derivative, increased LDLR mRNA and protein expression in HepG2 cells in a dose- and time-dependent fashion. These effects were apparent even under conditions of HMG-CoA reductase inhibition. Electrophoresis migration shift assays demonstrated that INV-403 activates SREBP2 but not SREBP1c, with immunoblot analysis showing an increased expression of the mature form of SREBP2. Knockdown of SREBP2 reduced the effect of INV-403 on LDLR expression. The activation of SREBP2 by INV-403 is partly mediated by Akt/GSK3β pathways through inhibition of phosphorylation-dependent degradation by ubiquitin-proteosome pathway. Treatment of C57Bl/6j mice with INV-403 for two weeks increased hepatic SREBP2 levels (mature form) and upregulated LDLR with concomitant lowering of plasma LDL levels. Transient expression of a LDLR promoter-reporter construct, a SRE-mutant LDLR promoter construct, and a SRE-only construct in HepG2 cells revealed an effect predominantly through a SRE-dependent mechanism. INV-403 lowered plasma LDL cholesterol levels through LDLR upregulation. These results indicate a role for small molecule approaches other than statins for lowering LDL cholesterol.